The Effect of Islamic Rural Banks (BPRS) on Regional Economies in Java - Siti Zulaikha, Mauizhotul Hasanah, Faris Kurnia Hakim, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
The financial sector in a region can spur the pace of economic movements, especially with the contribution of banks in the micro sector as an intermediary tool in channeling funds to productive investments that encourage the real sector, especially in the micro sector, which will produce aggregate output. The purpose of this study is to analyze the extent of the Islamic Rural Bank (BPRS), which is an Islamic microfinance institution for the economy on the island of Java. This study uses secondary data during the period from January 2016 to December 2018. This study uses the Ordinary Least Square Data Panel method. The empirical results show that part of Total Assets does not have a significant negative effect on GRDB. While the total financing and Third Party Funds (TPF) partially does not have a significant positive effect on GRDB. Also, simultaneously the overall independent variables together have a significantly positive effect on GRDB.